Предмет: Алгебра, автор: HeavenGirl

Разложите на множители:
1)  a^{4}- a^{8}
2)  frac{4a^{2} x^{4}  }{25} - frac{9y^{4} }{16}

Представьте выражение в виде произведения:
1)  x^{6}- (2y^{2}- x^{3})^{2}

Ответы

Автор ответа: DEMON666IM
0
a^4-a^8=(a^2-a^4)(a^2+a^4)=a^2(1+a^2)(a-a^2)(a+a^2)= \ a^4(1+a^2)(1-a)(1+a) \  \  frac{4a^2x^4}{25}- frac{9y^4}{16}= (frac{2ax^2}{5}- frac{3y^2}{4})( frac{2ax^2}{5}+ frac{3y^2}{4}) \  \ x^6-(2y^2-x^3)^2=(x^3-2y^2+x^3)(x^3+2y^2-x^3)=2y^2(2x^3-2y^2)= \ 4y^2(x^3-y^2)
Похожие вопросы